Altering the rehabilitation environment to improve stroke survivor activity: A Phase II trial. Issue 3 (March 2022) - Janssen, Heidi; Ada, Louise; Middleton, Sandy; Pollack, Michael; Nilsson, Michael; Churilov, Leonid; Blennerhassett, Jannette; Faux, Steven; New, Peter; McCluskey, Annie; Spratt, Neil J; Bernhardt, Julie; et al.
Background: Environmental enrichment involves organization of the environment and provision of equipment to facilitate engagement in physical, cognitive, and social activities. In animals with stroke, it promotes brain plasticity and recovery. Aims: To assess the feasibility and safety of a patient-driven model of environmental enrichment incorporating access to communal and individual environmental enrichment. Methods: A nonrandomized cluster trial with blinded measurement involving people with stroke ( n  = 193) in four rehabilitation units was carried out. Feasibility was operationalized as activity 10 days after admission to rehabilitation and availability of environmental enrichment. Safety was measured as falls and serious adverse events. Benefit was measured as clinical outcomes at three months, by an assessor blinded to group. Results: The experimental group ( n  = 91) spent 7% (95% CI −14 to 0) less time inactive, 9% (95% CI 0–19) more time physically, and 6% (95% CI 2–10) more time socially active than the control group ( n  = 102). Communal environmental enrichment was available 100% of the time, but individual environmental enrichment was rarely within reach (24%) or sight (39%). There were no between-group differences in serious adverse events or falls at discharge or three months or in clinical outcomes at three months. Conclusions: This patient-driven model of environmental enrichment was feasible and safe. However, the very modest increase in activity by people with stroke, and the lack of benefit in clinical outcomes three months after stroke do not provide justification for an efficacy trial.